A long-term dataset of sable isotopes in rainfall at the North American monsoon region in southern Sonora, Mexico - Mayte F. Reyes-Hernández; Jesús A. Castro-López; Tonantzin Tarín; Jaime Garatuza-Payán; David H. Encinas-Yépiz; Enrico A. Yépez (Data in Brief, 2022)
The objective of this work is to present a long-term dataset of water stable isotopes in rainfall samples from northwestern Mexico. These data is useful to generate a local meteoric water line as a reference tool for atmospheric and ecohydrological studies within the North American Monsoon region and to compare across the globe. This work shows the isotopic variation of the rainfall collected at a permanent location in Ciudad Obregon, Sonora, Mexico (27.511850, -109.956316), between 2014 and 2021. The isotopic composition of 138 rain samples was analyzed for both oxygen (δ18O) and deuterium (δ2H) with laser spectroscopy. The slope of the resulting local meteoric water line was m = 6.59 with an intercept of -1.15 (R² = 0. 91). During the monitored period at the studied region the presence of hurricanes, cold fronts and the hegemony of rainfall attributed to the North American Monsoon is recorded in the dataset.